KARAKTERISTIK DAN GAGASAN TEMATIK CERPEN ANAK DALAM LEMBAR KOMPAS ANAK - Ihramsari Akidah (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
This research aims to describe content and form, theme, as well as a thematic idea of children's short stories in the weekly Kompas Newspaper, in part “Children's Kompas, Stories”. The research data are words, sentences, or paragraphs that indicate the content, form, and theme. The sources of research data are the children's short stories in weekly Children’s Kompas Newspaper namely “Children's Kompas, Stories”. Data collection of the research used documentation, reading, taking notes, and making the data corpus. The research data was the content and form of children's short stories that the researcher analyzed based on the characteristics of children story's literature, namely simplicity of content and form. The theme analysis has been done by using Robert Stanton's theory. The result of the research shows that the children's short stories in the “Children's Kompas, Stories” in Kompas Newspaper, in terms of content and form, have a simple characteristic. The contents of the short story are about caring, prejudice, feelings of revenge, sadness, joy, courtesy, fable story, friendship at school, best friend, and other things that relate to the children’s world. In terms of form the story, children's short stories are generally realistic. However, another form of a realist short story, there is also in the form of a fable story, namely The Little Bear's Revenge Short Story. The language use of children's short story in "Children's Kompas, Stories" still need to be reviewed, specifically in the aspect of using diction, thus it can fully be said to have simple characteristics, whereas, in terms of how the story is told, it can be said to be simple. The theme of the children's short story in "Children's Kompas, Stories" is very various. The themes concern family, prejudice, revenge, mysterious friends, Chinese New Year celebrations without Grandma, health, politeness, memories, experiences while on vacation, justice, and friendship. The thematic ideas, which dominate all the short stories (data of the research), are didactic themes which mean cultivating educational values, moral values, as well as children's emotional sensitivity.